The Dutch Diving Fitness Test: defining the normal ranges of a test battery - Zimmermann, W. O. (Sport & Geneeskunde, 2009)
In 2000 the dutch diving fitness test (DDFT) for novice divers was introduced. Coaches can use the test to direct divers either to a recreational or a competitive training program. The test is a modification of a Mexican diving fitness test. The goal of this study is to define the normal ranges of the test results for Dutch schoolchildren. In the time frame of September 2004 through June 2008, 442 schoolchildren were tested on 10 items of physical performance. The measurement values are presented by gender and age group. Recommendations are made on the execution of the test. The results of this study are not only relevant to those who work in the field of springboard and platform diving. Parts of the test may be relevant to other professionals who test children in sports.